A Hybrid and Flexible Data Partitioner for Parallel SAMR - Steensland, Johan (Advanced Computational Infrastructures for Parallel and Distributed Adaptive Applications, 2009)
This chapter contains sections titled: Introduction: Why Realistic SAMR Simulations Require Hybrid Partitioning Parallel SAMR—–Related Work Designing a Flexible and Hybrid Partitioner Prepartitioning with Natural Regions Fractional Blocking for Speed and Quality Hybrid BI‐Level Partitioning The Organizer Experimentation Summary, Conclusions, and Future Work Acknowledgments References